Development of Education Facilities Based on Food Security as Agro-tourism through Community Empowerment in the Banyubiru Village, Banten - Heni Pujiastuti; Rudi Haryadi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
The purpose of community service activities is to improve the economy of the Banyubiru village community by making the Banyubiru village a resilience-based agro-tourism village. The method of implementing this activity was through the development of an educational vehicle, namely a maze of maize vehicle, a tomato picking vehicle, a hide-and-seek vehicle, a fishing mania vehicle and an animal feeding vehicle. All of these rides are carried out with community empowerment through mentoring and counseling. The method of implementing this activity is carried out using the learning community approach. The subjects of this activity were only selected by 50 communities, namely 25 men and 25 women. All of them are over 20 years old and less than 50 years old. The results of the implementation of community service activities indicate that there is an increase in community economic income. This can be seen from the addition of tourists in the past month. Every week the number of tourists rises 5%, from the number of visitors there. The response from tourists was 87% from the results of the interviews we had done. The results of tourist responses show very good results for tourists who visit. Furthermore, the results of observations on food security awareness of 75%, this means that the villagers are included in the good category and already know how to manage natural resources into agro-tourism villages based on food security.